The ecology of stomatopods in Matang waters with emphasis on Miyakea nepa and Oratosquillina perpensa / Ng Ying Pei - Ng, Ying Pei (2013)
An ecological study of the adult and larvae of stomatopods was carried out in the estuary of the Matang Mangrove Forest Reserve (Malaysia) and its adjacent coastal waters. The study investigated the spatial and temporal distribution of the adult stomatopod population; estimated the various parameters of stomatopod population dynamics; and elucidated the reproduction biology, larval ecology and feeding habits of stomatopods. Monthly trawl surveys (from September 2004 to February 2006) of adult stomatopods revealed four stomatopod species of the family Squillidae. Miyakea nepa (Latreille, 1828) was the most abundant species (16.36±12.48 ind/ha; 65.41%) followed by Oratosquillina perpensa (Kemp. 1911) (6.63±10.74 ind/ha; 26.51%), Harpiosquilla raphidea (Fabricius, 1798) (1.77±5.32 ind/ha; 7.08%) and Cloridopsis scorpio (Latreille, 1828) (0.25±0.80 ind/ha; 1.00%). In term of adult size, Harpiosquilla raphidea and Cloridopsis scorpio were the largest and smallest stomatopod collected, respectively. Although all four species shared the same general habitat, they were more abundant at particular sites, suggesting spatial differences and preference for environmental parameters. The spatial distribution of stomatopods juxtaposes with the continuous migration of juvenile shrimps from their estuarine nursery areas (mangroves, mudflats) to offshore grounds where they mature; the smallest species (Cloridopsis scorpio) in estuarine areas fed on the juvenile shrimps, the nearshore species (Miyakea nepa and Oratosquillina perpensa) fed on medium size shrimps, and the offshore species, Harpiosquilla raphidea (largest species) fed on adult shrimps. The four stomatopod species consumed a wide range of prey organisms, with shrimp as the most abundant food (26% to 80% by volume). The study shows the importance of the Matang mangrove estuary as an important source of prey organisms (for stomatopods) that migrate out of their nursery ground to offshore waters. Severe food competition among species is unlikely since shrimp fauna are diverse and occur in high abundance, and secondary diet specialization exists among the stomatopod species. The latter suggests some degree of trophic partitioning. PCA biplot ordination of stomatopod food items showed that Miyakea nepa is a generalist while three other species tend to specialize in their prey choice; Oratosquillina perpensa on crab, Harpiosquilla raphidea on fish and Cloridopsis scorpio on shrimp. Analysis of size frequency distribution of the two most abundant species showed that Miyakea nepa has a faster grow rate (growth parameter, K = 0.93 yr-1) and shorter lifespan (3.23 years) than Oratosquillina perpensa (K = 0.70 yr-1; lifespan = 4.29 year). Intensive fishing of Miyakea nepa and Oratosquillina perpensa in Matang due to their popularity as seafood has resulted in their overfishing (exploitation rate, E = 0.47 to 0.59). Therefore, sustainable fishing practices should be implemented. In general, the stomatopod populations were female-biased except Cloridopsis scorpio which was male-biased. Five stages of ovarian development of female Miyakea nepa, Oratosquillina perpensa, and Cloridopsis scorpio are discerned and described. Three stages of maturity of male Miyakea nepa and Oratosquillina perpensa based on cohorts of different mean penile lengths are described for the first time. Miyakea nepa and Oratosquillina perpensa breed throughout the year, each with two spawning peaks and one to two recruitment peaks.Planktonic stomatopod larvae were earlier sampled by bongo nets from the upper estuary to offshore waters from November 2002 to October 2003. The study has successfully identified four middle stages and two late stages of Cloridopsis scorpio larvae, whereby only three larval stages had been identified in other study. Collected larvae of Miyakea nepa only showed the late developmental stage. Stomatopod larvae distribution and abundance are affected by their environment including the availability of their potential food. Generally, Cloridopsis scorpio larvae were found mainly in the mangrove estuary while Miyakea nepa and the unidentified larvae were found throughout the coastal areas. Despite the temporal variations in abundance of newly recruited Cloridopsis scorpio, the results suggest only one spawning season in a year.